A comprehensive framework for quantitative risk assessment of organizational networks using FAIR-modified attack trees - Rana, Atul; Gupta, Sachin; Gupta, Bhoomi (Frontiers in Computer Science, 2024)
Attack trees are a widely used method for threat modeling and analyzing cyber-attacks in organizational networks. Assessing the risk associated with each individual node of an attack tree is crucial for understanding the overall risk of the attack. This paper presents a comparative study of different threat modeling methods and risk assessment approaches in organizational networks. The paper also presents a novel comprehensive approach for quantifying risk assessment of organizational networks based on attack trees modified according to factor analysis of information risk (FAIR) approach. Our results demonstrate the effectiveness of the novel approach in capturing the unique characteristics of different assets and their dependencies in an attack tree, leading to quantitative risk assessment.